Diversity and ecological impact of parasitic phytonematodes on greenhouse-grown Vegetable crops - Kurbanmuratovich, Raimov Shakhboz (American Journal of Biology and Natural Sciences, 2025)
In this article, the faunistic complex of phytonematodes identified during research in the greenhouses of Surkhandarya region is analyzed. According to the results of the research, 3984 individuals belonging to 51 species were recorded from the roots and pre-root soil of vegetable crops grown in the greenhouse, they are 5 genera, 9 subgenera, 13 large families, 20 families, 25 subfamilies. , belongs to 30 generations.